Pera Pola Komunikasi Humas dalam Membangun Citra Badan Pembinaan Hukum Nasional melalui Media Sosial Instagram @BPHN_KEMENKUM - Airin Deviana Amellya; Murtiadi; Roynaldi Arista (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The advancement of digital technology has encouraged government institutions to utilize social media as an effective public communication tool. This study aims to analyze the role of public relations communication patterns in building the image of the National Legal Development Agency (BPHN) through the Instagram platform. This research uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation of the official Instagram account of BPHN (@bphn.kemenkum) and relevant informants. The findings reveal that BPHN’s public relations apply an active, responsive, and participatory two-way communication pattern in managing content and public interaction. Features such as comments, direct messages, and interactive stories facilitate reciprocal communication that strengthens public engagement. Feedback evaluation is also conducted regularly as a basis for improving communication strategies. The study concludes that the communication pattern implemented by BPHN’s public relations significantly contributes to shaping an informative, transparent, and professional institutional image in the eyes of the public.